Blood Pressure Regulation by the Carotid Sinus Nerve - V Conde, Silvia (2022)
Funding Information: This study was partially supported by the GlaxoSmithKline Bioelectronics R&D ?Innovation Challenge. JS and BM were supported by a contract and a Ph.D. Grant from the Portuguese Foundation for Science and Technology Reference CEECIND/02428/2018 and PD/BD/128336/2017, respectively. This study received funding from the Fundação para a Ciência e Tecnologia (FCT) (UIDB/05704/2020).